The States of School Curriculum Administration for Developing Learning Achievement in Educational Opportunity Expansion Schools Under of Tak Primary Educational Service Area Office 1 - Sakolpattarasakun, Tharida; Siputta, Tussana (Journal of Modern Learning Development, 2023)
The research aimed to study the states of school curriculum administration for developing learning achievement in Educational Opportunity Expansion Schools Under of TAK Primary Educational Service Area Office 1. The samples used in the research were 217 school administrators, directors of academic subdivision and teachers in Educational Opportunity Expansion Schools Under of TAK Primary Educational Service Area Office 1 and the tool used to collect data was rating scale questionnaires. Then data was analyzed by some statics such as frequency, percentage, mean and standard deviation. The results of this research were as follow; the states of school curriculum administration for developing learning achievement in Educational Opportunity Expansion Schools Under of TAK Primary Educational Service Area Office 1, was at high level in 5 aspects when considering each aspect, it demonstrated that the planning and implementation of the curriculum at high level, follow by the using of curriculum, improving and developing the process curriculum management, the preparation of the curriculum, and the evaluation and respectively of curriculum was low level.